Medicinal Plant Analysis: A Historical and Regional Discussion of Emergent Complex Techniques - Fitzgerald, Martin; Heinrich, Michael; Booker, Anthony (Frontiers in Pharmacology, 2020)
The analysis of medicinal plants has had a long history and especially with regard to assessing a plants quality, the first techniques were organoleptic using the physical senses of taste, smell and appearance and gradually this has led on to more advanced instrumental techniques. Different countries have their own traditional medicines and currently China leads the way in terms of the number of publications focused on medicinal plant analysis and number of inclusion their Pharmacopoeia. The monographs contained within these publications give directions on the type of analysis that should be performed and for manufacturers, this typically means that they need access to more and more advanced instrumentation. We have seen developments in many areas of analytical analysis and particularly the development of chromatographic and spectroscopic methods and the hyphenation of these techniques. The ability to process data using multivariate analysis software has opened the door to metabolomics giving us greater capacity to understand the many variations of chemical compounds occurring within medicinal plants and allowing us to have greater certainty of not only the quality of the plants and medicines but also of their suitability for clinical research. Increases in technology have resulted in the ability to analyse and categories plants effectively and be able to detect contaminants and adulterants occurring at very low levels. However, advances in technology cannot provide us with all the answers we need in order to deliver high quality herbal medicines and the more traditional techniques of assessing quality remain as important today.